2002
DOI: 10.1046/j.1442-9993.2002.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of the Soft Tree Fern, Dicksonia antarctica Labill

Abstract: Environmental constraints on gas exchange, stomatal conductance and water relations were investigated in the Soft Tree Fern, Dicksonia antarctica , at sites across its natural distribution and in the glasshouse. Dicksonia antarctica exhibited strong stomatal response down to a vapour pressure deficit (VPD) of 0.25 kPa, an unusual characteristic when compared with other ground fern species. Net photosynthetic rate may be a response of the microenvironment prevalent during frond development, reflecting acclimato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…However, the conductance values observed for the tree fern Dicksonia antarctia (Hunt et al 2002) are comparable to those of mature E. giganteum stems, suggesting that pteridophyte hydraulic conductivity limitations may necessitate lower stomatal conductivity to avoid losing water faster than it can be replaced. Hydraulic conductivity of an E. giganteum stem may be greater than that of a tree fern because the pathway is much simpler in the former and leaves tend to represent a large proportion (25%-80%) of the hydraulic resistance in a plant (Nardini 2001;Sack et al 2003), and the higher end of this range seems plausible for highly compound tree fern lamina.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the conductance values observed for the tree fern Dicksonia antarctia (Hunt et al 2002) are comparable to those of mature E. giganteum stems, suggesting that pteridophyte hydraulic conductivity limitations may necessitate lower stomatal conductivity to avoid losing water faster than it can be replaced. Hydraulic conductivity of an E. giganteum stem may be greater than that of a tree fern because the pathway is much simpler in the former and leaves tend to represent a large proportion (25%-80%) of the hydraulic resistance in a plant (Nardini 2001;Sack et al 2003), and the higher end of this range seems plausible for highly compound tree fern lamina.…”
Section: Discussionsupporting
confidence: 46%
“…The tree fern Dicksonia antarcticum (Labill.) C. Presl, a long-lived species that is normally exposed to a wide range of environmental conditions, exhibits high stomatal sensitivity to VPD (Hunt et al 2002). Brodribb and Holbrook (2004) found that stomata of tropical dry forest pteridophytes were considerably more sensitive to decreased leaf water potential than associated angiosperms, demonstrating a more conservative response to water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their appeal to professional botanists, naturalists and the general public, tree ferns have been extensively studied and reported for their ecophysiological tolerances (Hunt et al 2002, Volkova et al 2009, 2010a, their horticultural and amenity use (Anon 1873, Attenborough 1997, Braggins & Large 2004, Jones & Clemesha 1976, Robbin 1985, Garrett 1998, Unwin & Hunt 1996, Wardlaw 1997 and their role as keystone species in forest regeneration dynamics (Gaxiola et al 2008, Ough & Murphy 2004, Smale et al 1997. The important role tree ferns play in the ecology of forest systems has been recognised in some of the earliest Australian and New Zealand forest ecological studies (Patton 1933, Petrie et al 1929, Pope 1924, 1926.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conductance values observed for the tree fern Dicksonia antarctia (Hunt et al 2002) are comparable to those of mature E. giganteum stems, suggesting that pteridophyte hydraulic conductivity limitations may necessitate lower stomatal conductivity to avoid losing water faster than it can be replaced. Hydraulic conductivity of an E. giganteum stem is likely to be greater than that of a tree fern because the pathway is much simpler in the former and leaves tend to represent a large proportion (25-80%) of the hydraulic resistance in a plant (Sack et al 2003, Nardini 2001, and the higher end of this range seems plausible for highly compound tree fern lamina.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, ferns from drier and more exposed habitats tend to exhibit strong stomatal response to increasing VPD (Losch et al 2007, Nobel et al 1984, Hietz and Briones 1998, although this response may be modified in ferns with leaf desiccation tolerance that close their stomata more slowly (Hietz and Briones 1998). The tree fern Dicksonia antarctica, a long-lived species that is normally exposed to a wide range of environmental conditions, exhibits high stomatal sensitivity to VPD (Hunt et al 2002). Brodribb and Holbrook (2004) found that stomata of tropical dry forest pteridophytes were considerably more sensitive to decreased leaf water potential than associated angiosperms, demonstrating a more conservative response to water stress.…”
Section: Stomatal Conductance Patterns Of Equisetum Giganteummentioning
confidence: 99%